A microbiological perspective of raw milk preserved at room temperature using hyperbaric storage compared to refrigerated storage - Duarte, Ricardo V. (2022)
The effects of hyperbaric storage (HS, 50–100 MPa) at room temperature (RT) on endogenous and inoculated pathogenic surrogate vegetative bacteria (Escherichia coli, Listeria innocua), pathogenic Salmonella enterica and bacterial spores (Bacillus subtilis) were assessed and compared with conventional refrigeration at atmospheric pressure for 60 days. Milk stored at atmospheric pressure and refrigeration quickly surpassed the acceptable microbiological limit within 7 days of storage, regarding endogenous microbiota, yet 50 MPa/RT slowed down microbial growth, resulting in raw milk spoilage after 28 days, while a significant microbial inactivation occurred under 75–100 MPa (around 4 log units), to counts below 1 log CFU/mL throughout storage, similar to what was observed for B. subtilis endospores. While inoculated microorganisms had a gradually counts reduction in all HS conditions. Results indicate that HS can not only result in the extension of milk shelf-life but is also able to enhance its safety and subsequent quality. Industrial relevance: This new preservation methodology could be implemented in the dairy farm storage tanks, or during milk transportation for further processing, allowing a better microbial control, than refrigeration. This methodology is very promising, and can improve food products shelf-life with a considerable lower carbon foot-print than refrigeration.